The Sanctions for Cancellation of Land Sale and Purchase Deeds Made in the Presence of Land Deed Making Officials in West Manggarai Regency - Fathullah, Rafli Ilham (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
The Deed of Sale and Purchase is an authentic Deed as the strongest evidence which has an important role in every legal relationship in people's lives which can clearly determine rights and obligations so as to guarantee legal certainty and at the same time avoid disputes. If a dispute occurs such as cancellation of an authentic deed. Authentic deed is the strongest piece of evidence and has perfect evidentiary power in court. This research aims to find out and analyze: 1) To find out and analyze what is the basis for Cancellation of a Land Sale and Purchase Deed made before a Land Deed Official in West Manggarai Regency Based on Supreme Court Decision No.9/Pdt.G/2018/PN Lbj; 2) To find out and analyze the position and legal consequences of canceling a land sale and purchase deed made before a land deed official in West Manggarai Regency based on Supreme Court Decision No.9/Pdt.G/2018/PN Lbj. The conclusions of the research results are: 1) The basis for the cancellation of the Land Sale and Purchase Deed made in the presence of the Land Deed Making Official in West Manggarai Regency stated that Defendant I had committed an act of fraud/deceit in making the Sale and Purchase Deed 39/2015, stated that the Sale and Purchase Deed Number: 39/2015, is invalid and has no legal force; 2) Position and Legal Consequences of Cancellation of the Land Sale and Purchase Deed made before the Land Deed Official in West Manggarai Regency declares that the land sale and purchase is void and the land is immediately transferred to the PLAINTIFF's name.